1990
DOI: 10.1111/j.1476-5381.1990.tb12050.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of extrapulmonary activity of angiotensin converting enzyme in intact tissue preparations

Abstract: 1 The activity of angiotensin converting enzyme (ACE) has been studied on functional parameters of intact isolated preparations of extrapulmonary tissues. The conversion of angiotensin I (A I) to angiotensin II (A II) and the cleavage of bradykinin (BK) were used as indicators of ACE activity. Captopril was employed as a specific inhibitor of ACE. 2 Captopril augmented the BK-induced contractions of the rat isolated uterus, the BK-and substance P-induced contractions of the guinea-pig ileum, and the BK-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…From this study and previous studies with rats (Patten, Adams, Dallimore, & Abeywardena, 2004), we have determined that the potency of angiotensin I compared to angiotensin II is about 5% in agreement with the literature (Law, 1971). However, the angiotensin I in this study is in the presence of a high dose of captopril which should inhibit approximately 13% conversion to angiotensin II by angiotensin converting enzyme (ACE) (Lembeck, Griesbacher, & Eckhardt, 1990) and block its action, but this was not the case. Indeed using colonic tissue from control rats, the contractile activity of angiotensin I could not be prevented by using inhibitors of other potential angiotensin I to angiotensin II converting pathways such as chymase by chymostatin (Cernucan et al, 2007;Heuston & Hyland, 2012) and cathepsin A by ebelactone B (Ostrowska et al, 2005) in the presence of captopril that was, however, completely blocked by losartan (Spak, Casselbrant, Olbers, Lonroth, & Fandriks, 2008) (results not shown).…”
Section: Discussionsupporting
confidence: 77%
“…From this study and previous studies with rats (Patten, Adams, Dallimore, & Abeywardena, 2004), we have determined that the potency of angiotensin I compared to angiotensin II is about 5% in agreement with the literature (Law, 1971). However, the angiotensin I in this study is in the presence of a high dose of captopril which should inhibit approximately 13% conversion to angiotensin II by angiotensin converting enzyme (ACE) (Lembeck, Griesbacher, & Eckhardt, 1990) and block its action, but this was not the case. Indeed using colonic tissue from control rats, the contractile activity of angiotensin I could not be prevented by using inhibitors of other potential angiotensin I to angiotensin II converting pathways such as chymase by chymostatin (Cernucan et al, 2007;Heuston & Hyland, 2012) and cathepsin A by ebelactone B (Ostrowska et al, 2005) in the presence of captopril that was, however, completely blocked by losartan (Spak, Casselbrant, Olbers, Lonroth, & Fandriks, 2008) (results not shown).…”
Section: Discussionsupporting
confidence: 77%
“…A previous study showed that ACE is essential for control of normal extracellular volume and arterial vasoconstriction, and these are affected by expression of the ACE gene, which is located on chromosome 17. An insertion/deletion (I/D) polymorphism has been identified, which generates three genotypes: D/D, I/D and I/I.…”
Section: Introductionmentioning
confidence: 99%
“…6 Most gene variants involve susceptibility loci, including the various psoriasis susceptibility genes (PSORS1-13), the gene for interleukin 12B and the gene for angiotensin-converting enzyme (ACE). [7][8][9] A previous study showed that ACE is essential for control of normal extracellular volume and arterial vasoconstriction, 10 and these are affected by expression of the ACE gene, which is located on chromosome 17. An insertion/deletion (I/D) polymorphism has been identified, which generates three genotypes: D/D, I/D and I/I.…”
Section: Introductionmentioning
confidence: 99%
“…However, while ACE inhibitors largely increase bradykinin-induced oedema , used alone, they do not modify plasma exudation induced by SR Similarly, captopril does not affect the vasodilatory effect of SP in hamster cheek pouch (Gao and Rubinstein 1995). In fact, comparatively to bradykinin, SP is a poor substrate for ACE (Skidgel et al 1984;Lembeck et al 1990). In rats, the increase of vascular permeability induced by SP was enhanced by ACE inhibitors in combination with phosphoramidon, a NEP inhibitor, or with diprotin A, a DAP IV inhibitor.…”
Section: Discussionmentioning
confidence: 99%